TRADING BUSINESS IN THE PERSPECTIVE OF BUSINESS LAW - Há»c viá»‡n TÆ° phÃ¡p; Aris Prio Agus Santoso (International Journal of Law and Legal Ethics, 2022)
In Era 5.0, the trading business is increasingly widespread and much-loved by millennials because it promises fantastic income and income. Recently, fake investment news has spread because gambling is disguised as if trading is deceiving investors. Many affiliates and influencers sometimes offer unrealistic profits as a marketing strategy to the detriment of their customers. The purpose of this study is to find out how the trading business is viewed from the legal aspect of business. This research method uses a normative juridical approach with secondary data collection obtained from the literature and legislation. The results of this study were analyzed qualitatively to answer the formulation of the problem. The results of the study show that actually the engagement that occurs between affiliates or influencers with their customers or investors is in accordance with Article 1320 of the Civil Code, but if this trading business leads to online gambling then this becomes a criminal act as regulated in Article 303 of the Criminal Code which carries a maximum prison sentence of 10 years. In Thailand, gambling is prohibited by the B.C. Gambling Act. 2478, however, on October 25, 2011, the Government approved the draft Gambling Bill, which legalized gambling debt. Even so, gambling debts must still be legally processed in court. Gambling must be controlled by the government both in Indonesia and Thailand to improve the economic, social and moral status of the community because the trading business that leads to gambling is very detrimental to one party.